Multiple Cooper minima in ground state E2 photoionization of high Z atoms. (August 2015) - Banerjee, Tanima; Mandal, Ankur; Deshmukh, Pranawa C; Manson, Steven T
Synopsis: Quadrupole photoionization from valence and intermediate subshells of atomic mercury, radon and radium have been studied in the present work. Multiple Cooper minima in the E2 channels have been found even when only intra-shell inter-channel coupling is included, in contrast with the dipole case in which multiple Cooper minima were found only when inter-shell interchannel coupling was included.